2001
DOI: 10.1007/s004020000181
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year results of the Müller CoCrNiMo Straight Stem

Abstract: Between September 1980 and May 1982, 112 primary unilateral total hip arthroplasties with the original cemented M. E. Müller Straight stem (manufactured from Protasul-10, a CoCrNiMo alloy) were inserted in 109 consecutive patients, all combined with non-cemented, non-coated polyethylene RM cups. Forty-three patients (40%) died during the follow-up period, all with the implant in place. Of the 66 surviving patients, 2 (1.8%) were lost to follow-up, and 7 (6.3%) were unable to attend the 15-year clinical and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In the Swedish prosthesis register, the 10-year results of the Müller straight stem prosthesis are superior to those of the Charnley prosthesis [12]. In other studies, a 15-year survival rate of 88% and a 10-year survival rate of 94% were found for the chromium-cobalt design [7,19]. Good results were also reported in other studies with shorter follow-up examination intervals [11,22,25].…”
Section: Introductionmentioning
confidence: 84%
“…In the Swedish prosthesis register, the 10-year results of the Müller straight stem prosthesis are superior to those of the Charnley prosthesis [12]. In other studies, a 15-year survival rate of 88% and a 10-year survival rate of 94% were found for the chromium-cobalt design [7,19]. Good results were also reported in other studies with shorter follow-up examination intervals [11,22,25].…”
Section: Introductionmentioning
confidence: 84%
“…The films were rated according to the Gruen zone system for the femoral component and according to De Lee and Charnley for the acetabular component ( Figure 1) [9] . Loosening was defined as follows: potential loosening: radiolucency (linear/focal) < 2 mm; probable loosening: linear radiolucency > 2 mm; focal radiolucency > 5 mm; definitive loosening: linear radiolucency > 2 mm all around [1,9] (Table 1). Subsidence of the stem was measured as the difference between the highest point of the prosthesis shoulder and the horizontal sclerotic line above the shoulder.…”
Section: Methodsmentioning
confidence: 99%
“…The original Müller straight stem prosthesis falls into this category. The original Müller straight stem prosthesis has shown excellent results at 10 to 15 years [1][2][3][4] . The 10 year survival rate for the stem ranges from 91.2% to 98.3% [3,5] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations